2010
DOI: 10.1177/159101991001600312
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage Rates and Outcomes When Using up to 100 mg Intra-Arterial t-PA for Thrombolysis in Acute Ischemic Stroke

Abstract: This work presents a unique single center experience with intra-arterial delivery of tissue plasminogen activator (t-PA) doses as high as 100mg for thrombolysis. Hemorrhage volumes, hemorrhage rates, clinical outcomes and radiographic outcomes were assessed. Prospectively collected angiographic, clinical and laboratory information on 67 consecutive patients with acute ischemic stroke involving either the m1 segment of the middle cerebral artery, the intracranial internal carotid arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The results show that there was a significant difference in disease onset time and urokinase dosage between patients with and without bleeding complications. The probability of bleeding increases as the disease onset time and urokinase dosage increase (27). In contrast to previous findings, there is no statistical difference in disease onset age, preoperative NIHSS score and recanalization time between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that there was a significant difference in disease onset time and urokinase dosage between patients with and without bleeding complications. The probability of bleeding increases as the disease onset time and urokinase dosage increase (27). In contrast to previous findings, there is no statistical difference in disease onset age, preoperative NIHSS score and recanalization time between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Higher doses of alteplase delivery need to be used with caution. Accounting for cumulative reperfusion rates for M1 and carotid terminus occlusion higher upper limit doses has been shown to improve reperfusion rates 22 and increase hemorrhage rates. Furthermore, at 1 mg per minute, the alteplase delivery time is longer; however, the typical microcatheter placement time within the thrombus is more rapid than placement of a thrombectomy device.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients who received IAT (together with other endovascular treatments) after ≥8 hours, Natarajan and colleagues documented approximate rates of 33% for both mortality at 90 days and immediate hemorrhage (subarachnoid and intracranial) [ 21 ]. The risk of ICH with IAT may be associated not only with the dose of thrombolytic used during IAT [ 22 ], but also with the severity of the stroke [ 23 ]. Regarding other complications, the PROACT II trial reported that 1% of patients receiving IAT with recombinant prourokinase experienced anaphylaxis and 7% experienced systemic hemorrhage [ 13 ].…”
Section: Introductionmentioning
confidence: 99%